The Influence of Knowledge and Risk Perception on Food Label Reading Behavior among Adolescents in Rural and Urban Areas of Bogor - Hajijah, Rengganis Novyanti; Retnaningsih, Retnaningsih (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Reading food labels is one way consumers learn about the products they buy. This study determined the influence of knowledge and risk perception on food label reading behavior among adolescents in rural and urban Bogor. This study had a cross-sectional design. Purposive sampling was used to gather 132 participants, including 66 adolescents in rural areas and 66 adolescents in urban areas. The results showed that more than half of the participants had moderate knowledge of food labeling. The knowledge of the rural and urban samples was the same. Operational risk was the most perceived risk for both the rural and urban samples. There were no significant differences in all dimensions of risk perception between rural and urban youths. The average food label reading behavior score in rural areas was higher than that in urban areas. Psychological risk perception influences food label-reading behavior in rural areas. Overall, functional risk perception influenced food label-reading behavior. Based on these results, it is necessary to increase education on the importance of food labels to build good risk perception so that food label reading behavior increases.